A Case Report on Methotrexate Overdose Induced Pancytopenia and Mucocutaneous Ulcerations - Srinivasa, Brunda Mysore; Padmini, SN; Kumar, Praveen; Philip, Aneena Annu; Presannan, Athira K; Thomas, Riny; Arif, Arshiya (Indian Journal of Pharmacy Practice)
Methotrexate (MTX) is commonly used in autoimmune conditions including rheumatoid arthritis, psoriasis, lupus, sarcoidosis and eczema due to its anti-inflammatory and immunosuppressive effect. The following report describes the case of a 55 year old female presenting with complaints of erythematous rashes over the limbs, oral and vaginal haemorrhagic mucositis. She was previously diagnosed with psoriasis and was on MTX 15mg weekly but the patient had taken it continuously resulting in toxicity. She was hospitalised, MTX withdrawn and treated with folinic acid. Our case highlights the importance of counselling in order to ensure adherence to the correct MTX treatment regimen to prevent toxicity and its serious effects.
Keywords: Methotrexate; Overdose; Psoriasis; Pancytopenia; Mucositis.